2022
DOI: 10.1186/s13102-022-00584-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic restrictions on physical activity and mental health status of Iranian people

Abstract: Background Coronavirus-19 (COVID-19) is a highly contagious disease caused by acute respiratory syndrome that can negatively impact physical activity as well as mental health of people in the world. Since Iran is one of the countries deeply affected by the COVID-19 pandemic, therefore, the aim of this study was to investigate the impact of the COVID-19 pandemic restrictions on physical activity behaviours, as well as on mental health indicators among Iranian people. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Multiple studies have supported this hypothesis, which has repeatedly shown a decrease in PA during restriction periods (24)(25)(26)(27). Countries around the world are addressing PA as a result of COVID-19, and research is linking it to physical, psychological, and mental health (28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 98%
“…Multiple studies have supported this hypothesis, which has repeatedly shown a decrease in PA during restriction periods (24)(25)(26)(27). Countries around the world are addressing PA as a result of COVID-19, and research is linking it to physical, psychological, and mental health (28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 98%
“…Most studies show that the decrease of physical activity during the COVID-19 period may lead to mental health problems of adolescents [2]. Some studies also show that there is a no significant relationship between physical activity changes and other psychological indicators during the COVID-19 period [6]. This study explored the changes in the relationship between physical activity and mental health of the two groups based on whether they were infected with COVID-19.…”
Section: Plos Onementioning
confidence: 99%
“…Research has shown that COVID-19 is associated with lower levels of physical activity, lower self-esteem, and higher social anxiety. Whether the relationship between the change of physical activity level and self-esteem, social anxiety has changed after the COVID-19 epidemic deserves further exploration [6]. Therefore, this paper explores the internal relationship between physical activity and mental health of adolescents after the COVID-19 epidemic, and whether social anxiety and self-esteem mediate these relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, researches showed that the lockdown during the pandemic would induce the negative change in eating habits, lifestyle, and health conditions ( 8 11 ). Study showed that there are significant differences from before to during the pandemic in people’s physical activity (significant decreases), self-esteem (significant decreases), and social physical anxiety (significant increases) regardless of their gender due to the restrictions ( 12 ). People also experienced different degrees of disruption in their daily routines and physical activity during the pandemic ( 13 ).…”
Section: Introductionmentioning
confidence: 96%